Câncer de cabeça e pescoço : tendência de mortalidade e análise comparativa das técnicas de hibridização in situ, RT-qPCR e p16 para diagnóstico de infecção por HPV - Sant'Anna, Jéssica Graça (2024)
In Brazil, regional disparities in mortality rates from head and neck squamous cell carcinoma (HNSCC) are high. Infection with high-risk oncogenic human papillomavirus (HR-HPV) is an important risk factor, associated with an increase in cases of oropharyngeal squamous cell carcinoma (OPSCC) in Brazil and globally. This study analyzed mortality trends from HNSCC between 1998 and 2017 in Espírito Santo, Brazil (ES-BR), and methods for detecting HR-HPV in OPSCC using messenger RNA (mRNA) E6 by RT-qPCR, mRNA E6/E7 by in situ hybridization (RNA-ISH), and immunohistochemistry for p16 expression (IHC-p16) in Espírito Santo, Brazil (ES-BR) and Bogotá, Colombia (BO-CO). The mortality trend methodology was conducted in reference hospitals in ES-BR, using mortality data from DATASUS, the Mortality Information System (SIM), and data from the Brazilian Institute of Geography and Statistics (IBGE). Clinicopathological characteristics and HPV status of the studied sites were analyzed, and HPV detection methods were compared using RNA-ISH and IHC-p16 with RT-qPCR as the standard for sensitivity and specificity analysis. Between 1998 and 2017, mortality from HNSCC increased in ES, especially among men, rising from 48.96 to 58.24 deaths per 100,000 inhabitants. Regarding anatomical subsites, men showed an increase in deaths from oral cavity, oropharyngeal, and laryngeal cancers, while women’s increase was limited to oral cavity cancer. Regarding HR-HPV, samples from ES showed lower frequencies of infection compared to those from BO. Lymph node metastasis was associated with a worse prognosis, while HPV-positive patients had better survival. Smoking negatively impacted survival. Detection methods for HR-HPV, such as IHC p16, RNA-ISH, and RT-qPCR, showed statistical significance. The results show an increase in HNSCC mortality in ES, especially among men and in OPSCC. The IHC p16 technique had high sensitivity, while RNA-ISH showed high specificity. Regional strategies and advanced diagnostics are crucial for managing HNSCC